Implementasi Google Cloud Pub/Sub menggunakan Metode Subscription Pull dalam Pengiriman Data Promosi Toko di PT XYZ - Richardo, Daniel; Kurniasih, Tatit (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
As a company adopts a distributed business model, scalability issues often arise in the distribution of data from server to client. PT XYZ, as one of the companies facing this challenge, frequently encounters delays and request blocking when using synchronous communication models such as RESTful API. Additionally, there is resource and time wastage on the server side as it has to handle store requests one by one, resulting in losses for the store due to delayed access to required data for business processes. This research proposes a solution to address these issues by implementing a publish/subscribe communication model. Through the implementation of this architecture, clients and servers are separated by a broker, namely Google Cloud. Pub/sub technology is implemented using the Python programming language with the Waterfall development method. The results of this research include the design of a client-side application capable of receiving data from a previously deployed broker. Test results demonstrate that the client can receive data at any time without disrupting the data fetching process for other clients.